Polyol-mediated zinc oxide nanoparticles using the refluxing method as an efficient photocatalytic and antimicrobial agent - Walunj, Payal; Roy, Arpita; Jadhav, Vikram; Athare, Pragati; Dhaygude, Akshay; Aher, Jayraj; Algethami, Jari S.; Lokhande, Dnyaneshwar; Alqahtani, Mohammed S.; Bhagare, Arun; Alghamdi, Saad; Eltayeb, Lienda Bashier; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Nanomaterials have attracted more curiosity recently because of their wide-ranging application in environmental remediation and electronics devices. The current study focuses on zinc oxide nanoparticle (ZnO NPs) simple production, characterization, and applications in several fields like medicinal and photocatalytic degradation of dyes. The nonaqueous-based reflux method is helpful for ZnO NPs synthesis; the procedure involves refluxing zinc acetate dihydrate precursor in ethylene glycol for three hours in the absence of sodium acetate; in which the refluxing rate and the cooling rate are optimized to get the desired phase, and unique morphology of polyol mediated ZnO NPs, it has been achieved using capping agent TBAB (Tetra-butyl ammonium bromide), and precursor zinc acetate dihydrate. Polyol-mediated ZnO-NPs were structurally characterized by UV-Vis, FTIR, XRD, and FESEM. The results show that the material is pure and broadly aggregated into spherical nanoparticles with an average particle size of 18.09 nm. According to the XRD analysis, heat annealing made the crystallites larger and favoured monocrystalline. These results and the low cost of making polyol-mediated ZnO-NPs demonstrate photocatalytic and antimicrobial properties.